**Re: HELPPPPP please**
TchrWill said:

4x^2=1

DIvide through by 4 yielding x^2 = 1/4

Take the square root of both sides yielding x = 1/2

11x^2-12+1=0

Using the quadratic equation,

x = [12+/-sqrt(12^2 - 4(11))]/22

x = [12+/-sqrt(100)]/22

x = [12+10]/22 = 1 or [12-10]/22 = 1/11

Above is not correct - as posted:

\(\displaystyle 11x^2 -12 + 1 = 0\)

\(\displaystyle 11x^2 - 11 = 0\)

\(\displaystyle 11x^2 = 11\)

\(\displaystyle x^2 = 1\)

\(\displaystyle x = \pm 1\)

___________________________________________

x^2-12=0

Adding 12 to both sides yields x^2 = 12

Taking the square root of both sides yields x = sqrt12 = sqrt(4(3)) = 2sqrt3 = 3.4641[/quote]